2017
DOI: 10.20960/nh.1561
|View full text |Cite
|
Sign up to set email alerts
|

Consenso sobre la evaluación y el tratamiento nutricional de los trastornos de la conducta alimentaria: anorexia nerviosa

Abstract: Anorexia nervosa is the most common psychiatric disease among young women and it is assumed to be of multifactorial origin. Diagnostic criteria have recently been modified; therefore amenorrhea has ceased to be a part of them. This disease shows a large variability in its presentation and severity which conditions different therapeutic approaches and the need to individualize the treatment, thus it is indispensable a multidisciplinary approach. The goals are to restore nutritional status (through an individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
3
0
4
Order By: Relevance
“…In one study in hospitalized teenagers with anorexia nervosa, the combination of oral nutritional supplements and nasogastric feeding in addition to natural feeding produced a shorter duration of hospitalization than the combination of natural feeding with either oral nutritional supplement or nasogastric feeding (27). Due to ndings such as these, clinical guidelines state that the expected bene cial effects of nutritional supplementation in pAN are (13): reduction of the known adverse effects associated with malnutrition (increased morbidity and mortality, and reduced quality of life); during the rst half of treatment, better and faster nutritional recovery along with the agreed diet; reduction of hospital stays; shortening of treatment duration; avoidance of early satiety. The latter is because it has been shown that in pAN there is a delayed gastric emptying of solid but not of liquid meals, therefore liquid supplementations can be a well-tolerated intervention, especially at the beginning of the intervention, when gastric emptying is more delayed (14).…”
Section: Discussionmentioning
confidence: 99%
“…In one study in hospitalized teenagers with anorexia nervosa, the combination of oral nutritional supplements and nasogastric feeding in addition to natural feeding produced a shorter duration of hospitalization than the combination of natural feeding with either oral nutritional supplement or nasogastric feeding (27). Due to ndings such as these, clinical guidelines state that the expected bene cial effects of nutritional supplementation in pAN are (13): reduction of the known adverse effects associated with malnutrition (increased morbidity and mortality, and reduced quality of life); during the rst half of treatment, better and faster nutritional recovery along with the agreed diet; reduction of hospital stays; shortening of treatment duration; avoidance of early satiety. The latter is because it has been shown that in pAN there is a delayed gastric emptying of solid but not of liquid meals, therefore liquid supplementations can be a well-tolerated intervention, especially at the beginning of the intervention, when gastric emptying is more delayed (14).…”
Section: Discussionmentioning
confidence: 99%
“…▪ Estado de ánimo: Las personas con depresión y bajo estado de ánimo suelen elegir con mayor frecuencia alimentos poco saludables pero muy palatables con el objetivo de disfrutar más de la comida (Gómez et al, 2018).…”
Section: Psicológicosunclassified
“…Otras conductas destinadas al control del peso, tales como consumo disminuido o aumentado de líquidos, masticar frecuentemente chicle sin azúcar, abuso de endulzantes, uso de diversas sustancias con el fin de suprimir el apetito o bajar de peso (cafeína, té, tabaco -fumar-, drogas ilegales y suplementos nutricionales), y abuso de otros suplementos, como barras y polvos de proteína, y creatina (esto último en varones activos en el gimnasio) 2,[52][53][54] .…”
Section: Presentación Clínicaunclassified